THE ROLE OF VILLAGE GOVERNMENT IN PUBLIC INFORMATION DISCLOSURE (CASE STUDY IN SUGIHWARAS VILLAGE, CANDI DISTRICT, SIDOARJO REGENCY) - Luthfiyah, Amirotul; Usrotin Choiriyah, Ilmi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the role of the Sugihwaras Village Government in implementing public information disclosure as part of transparent, participatory, and accountable governance. Method: Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, documentation, and digital questionnaires distributed to village officials and the community. The analytical framework adopts Biddle's role theory, which emphasizes how individuals understand, internalize, and perform their expected social roles within an organizational context. Results: The research findings reveal that although infrastructures such as the Village Information System (SID) and the Information and Documentation Management Officer (PPID) have been established, the implementation of information transparency remains suboptimal. Challenges include unclear role expectations among village officials, limited human resource capacity, weak inter-role coordination, and low digital literacy within the community. Furthermore, role ambiguity and passive disposition among implementers have reduced the effectiveness of the information disclosure policy. Therefore, the success of this policy requires clear role structuring, consistent role communication, support from higher-level government structures, and active public participation. Novelty: This study contributes theoretically by applying role theory in public administration and practically by offering recommendations to strengthen role alignment in village governance.